PEMANFAATAN KAYU HASIL PENJARANGAN DARI HUTAN TANAMAN (HTI) UNTUK PEMBUATAN PRODUK INTERIOR - Jamal Balfas (Jurnal Penelitian Hasil Hutan, 1994)
Regrowth forests in Indonesia have eesentially been developed since several centuries ago particularly in Java for the luxury timber species such as teak (Tectona grandis), rasamala (Altingia excelsea), Sonokeling (Dalbergia latifolia), mahoni (Swietenia spp.), etc. In this system the young plantation always have surplus trees which are likely to cause overcrowding and furthermore reducing the growth of bigger trees. Accordingly, at certain ages (depending on species, site class, etc.) the surplus trees are thinned out regularly throughout the planting cycle to achieve a maximum timber yield. Each thinning will produce a plenty of small-sized logs which are generally considered too small for sawmills or plymills. Such logs are commonly used for firewood or other low value products, or even left to rot in the forest floor.This study investigated a technical possibility of turning the waste wood into useful interior products, such as table top, furniture blanks, window and door frames, etc. Thinned logs of two wood species, tusam (Pinus merkusii) and damar (Agathis lorantifolia) collected from a government company plantation in West Java were used in this study. Procedures of saving logs into boards, drying and further machining processes were basically undertaken according to the convetional practices. Furniture blanks, table tops and large planks were manufactured by side-jointing and or laminating thin boards with a simple clamping procedures. Polyvinyl acetate and resorcinol formaldehyde adhesives were uesd for constructing blanks and planks respectively. The results revealed thar interior products made up from the thinned logs possessed a comparable characteristics to those made from mature timbers. Table tops and blanks built from three layers of laminates gave a better concictency in shape and straightness than the one layer side joint panels.